Engendering Violence in Papua New Guinea - Jolly, Margaret; Stewart, Christine; Brewer, Carolyn (ANU Press, 2012)
This collection builds on previous works on gender violence in the Pacific, but goes beyond some previous approaches to 'domestic violence' or 'violence